2022
DOI: 10.3390/agronomy12040803
|View full text |Cite
|
Sign up to set email alerts
|

Response in Physiological Traits and Antioxidant Capacity of Two Cotton Cultivars under Water Limitations

Abstract: Deficit irrigation water (DW) is one of the main stress factors that negatively affect cotton cultivation. Hence, the identification of cotton cultivars tolerant to DW and sandy soil conditions is particularly needed. Understanding the response of cultivars to DW is essential for estimating water needs. Besides, by understanding the physiological and antioxidant status, reflecting distinct growth, yield, and fiber quality traits under DW, the cultivar tolerant to DW can be identified in the early stage of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…One unit of SOD is the amount of enzyme needed to dismutase 50% of available superoxide radicals [ 40 ]. The POD enzyme activity was detected at 470 nm and one unit is the amount of enzyme that changes the absorbance by 0.01 per min of guaiacol oxidation [ 41 ]. CAT enzyme activity was determined by reading the absorbance at 240 nm.…”
Section: Methodsmentioning
confidence: 99%
“…One unit of SOD is the amount of enzyme needed to dismutase 50% of available superoxide radicals [ 40 ]. The POD enzyme activity was detected at 470 nm and one unit is the amount of enzyme that changes the absorbance by 0.01 per min of guaiacol oxidation [ 41 ]. CAT enzyme activity was determined by reading the absorbance at 240 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Ayele et al (2020),Yehia (2020), andEid et al (2022) observed the same trend when compared to water-de cit stress conditions; cotton genotypes in normal irrigation conditions showed higher seed cotton yield, which ranged from 11.12% by G3 to 28.03% by G7, suggesting genetic variability in eleven studied genotypes for drought tolerance. Also,Grzesiak et al (2019) andSun et al (…”
mentioning
confidence: 55%
“…Cotton genotypes tolerant to drought stress and sandy soil conditions are especially needed in areas where drought is a major stress factor affecting cotton agriculture (Eid et al 2022). Results of combined ANOVA exhibited statistically signi cant differences (p ≤ 0.05 or 0.01) among genotypes (G), years (Y), and GY interaction for seed cotton yield under normal irrigation and water-de cit stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the elevated CAT and POD activities to decompose H 2 O 2 to oxygen and water molecules. Enhanced activity of antioxidant enzymes in response to drought stress was also reported in soybean (Moloi and Merwe 2021), cotton(Eid et al 2022), and silymarin (ElSayed et al 2019). Alterations in ribosomal proteins have also been reported in drought-stressed foxtail millet(Pan et al 2018) and salt-stressed cucumber(Du et al 2010).…”
mentioning
confidence: 67%